Governance of patient‐centred care: A systemic approach to cancer treatment. (17th August 2020) - Gorod, Alex; Hallo, Leonie; Merchant, Susan
Abstract: Currently, policymaking in cancer treatment is based on a reductionist approach and does not consider the differing views of multiple stakeholders in a systemic fashion. Non‐integrated views are not representative of the totality of the real‐life treatment context, and policymakers need to capture that holistic representation in their decision making. This paper uses a 'systems thinking' approach to propose a holistic way of capturing different stakeholders' views and integrating these into optimal treatment. Key stakeholders operate within their own system, as well as within the overarching complex system of cancer treatment care. An integrated view will enable policymakers to better understand the various issues involved and invoke a more holistic governance approach that encourages greater integration and emergence. Subject matter experts in Australia were consulted to provide narratives that were used to construct individual systemic views (systemigrams) to represent the constructivist perspectives of two key stakeholder groups: patients and oncology nurses. Semi‐structured interviews were conducted to validate the representativeness of the systemigrams created. The systemigrams that captured the perceptions and objectives of patients and nurses were found to be significantly different from each other. Understanding that individual views are only a part of the complex system can lead to a better appreciation of failures within cancer treatment and how to address these through optimal governance. Dynamic integration of differing perspectives in the cancer treatment journey is important. Recognizing and encouraging emergent behaviour among key stakeholders will enable effective governance. Management in cancer care is currently largely undertaken through individual silos with little interaction between those silos. This paper presents a new way of visualizing and conceptualizing governance of cancer treatment that will make governance more holistic and will improve patient‐centred care.